Operador maximal de Hardy-Littlewood em espaços de Sobolev. - Marques Filho, Peron (2019)
In this work we study the extension of the Hardy-Littlewood-Wiener theorem of harmonic analysis for Sobolev spaces W^1,p(R^n) when p > 1. This Theorem is due to Juha Kinnunen.